PERSEPSI PETANI KENTANG TERHADAP AKSES LEMBAGA KEUANGAN SYARIAH DI KECAMATAN PASIRWANGI, KABUPATEN GARUT - Nabila Fazrin Maulani; Eliana Wulandari (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Pasirwangi Subdistrict is one of potato production centers in West Java. The need of finance from sharia financial institutions because their lack of capital, uncertain product availability and high production input prices. Sharia finance institution  put less interest in financing agricultural business because agricultural sector have a high risk. This research aims to analyze potato farmers' perceptions of access sharia finance institutions. This research applied descriptive analysis in particular cross tabulation. The results showed that there were convenience, continuity, and flexibility access sharia finance institution, but there were not availability access sharia finance institution